(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The sport of wrestling calls for a well-balanced fusion of physical fitness, tactical skill, mental toughness, and character development, especially for young competitors. This article explains the crucial value of developing new wrestlers while highlighting the sport’s diversity. We give a thorough training programme that includes strength training, skill practise, agility improvement, mental conditioning, and recuperation techniques through a thorough methodical approach. The objective is to develop young wrestlers into strong athletes while also instilling discipline, respect, and persistence qualities. The conclusion highlights the benefits of such training, which include both sporting brilliance and the development of transferable life skills.